2003
DOI: 10.5194/acpd-3-4549-2003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A box model study on photochemical interactions between VOCs and reactive halogen species in the marine boundary layer

Abstract: Abstract. A new chemical scheme is developed for the multiphase photochemical box model SEAMAC (size-SEgregated Aerosol model for Marine Air Chemistry) to investigate photochemical interactions between volatile organic compounds (VOCs) and reactive halogen species in the marine boundary layer (MBL). Based primarily on critically evaluated kinetic and photochemical rate parameters as well as a protocol for chemical mechanism development, the new scheme has achieved a near-explicit treatment of oxidative degrada… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 105 publications
(229 reference statements)
0
4
0
Order By: Relevance
“… CHCl2O2+NOCHCl2normalO+NO2 CHCl2O2+NO3CHCl2normalO+NO2+O2 and are not phosgene forming channels as CHCl 2 O is expected to decompose to CHClO + Cl (e.g., Catoire et al, ). The atmospheric fate of CHClO is poorly known but sinks are expected to include atmospheric removal via heterogeneous and multiphase deposition processes (e.g., Ko et al, ; Toyota et al, ).…”
Section: Model and Experimentsmentioning
confidence: 99%
“… CHCl2O2+NOCHCl2normalO+NO2 CHCl2O2+NO3CHCl2normalO+NO2+O2 and are not phosgene forming channels as CHCl 2 O is expected to decompose to CHClO + Cl (e.g., Catoire et al, ). The atmospheric fate of CHClO is poorly known but sinks are expected to include atmospheric removal via heterogeneous and multiphase deposition processes (e.g., Ko et al, ; Toyota et al, ).…”
Section: Model and Experimentsmentioning
confidence: 99%
“…The most important oxidants for DMS are hydroxyl (OH) and nitrate (NO 3 ) radicals. Halogen compounds, especially Cl atoms and BrO radicals, have also recently been suggested as oxidants for DMS in the marine environment [ Toyota et al , 2004; Wingenter et al , 2005; Barnes et al , 2006]. By contrast, DMS oxidation by O 3 in the gas phase is thought to be unimportant, although this conclusion is based on only a small number of laboratory studies [ Martinez and Herron , 1978].…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous laboratory and theoretical investigations of the mechanism for gas phase DMS oxidation, establishing OH and NO 3 as the main oxidants and leading to various products, which will be discussed later [ Hynes et al , 1986; Yin et al , 1990; Jensen et al , 1992; Le Bras et al , 1993; Turnipseed et al , 1996; Capaldo and Pandis , 1997; Ravishankara et al , 1997; Davis et al , 1999; Arsene et al , 2001; Williams et al , 2001; Lucas and Prinn , 2002, 2005]. Several recent studies have pointed out that Cl atoms and BrO radicals could play an important role as DMS oxidants [ Keene et al , 1996; Knipping et al , 2000; Sciare et al , 2000; Toyota et al , 2004; Dyke et al , 2005; Wingenter et al , 2005; Barnes et al , 2006]. The subsequent reactions, yields, and end products arising from each of the possible oxidants OH, NO 3 , and halogens, are important to the impact of DMS on the global source for nss aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…During daytime, the cloudy part of the MBL is dynamically decoupled from the subcloud layer, which confines the active halogen chemistry to the subcloud layers. Toyota et al (2004) have suggested that organic bromine may form from inorganic bromine compounds in the MBL. The diurnal variation of gas-and aqueous-phase bromine is reversed compared to the cloud-free MBL, which might help resolve discrepancies in the diurnal variations between previous model studies and field experiments (e.g., Rancher and Kritz, 1980;Sander et al, 2003a;Pszenny et al, 2004).…”
Section: Model Resultsmentioning
confidence: 99%